2016
DOI: 10.5978/islsm.16-or-17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibacterial Effects of 810 and 980- nanometer Diode Lasers on Enterococcus Faecalis in the Root Canal System-An <i>in vitro</i> study

Abstract: Background and aim:Use of laser technology in endodontics has greatly increased in the recent years due to the introduction of new wavelengths and methods and optimal antimicrobial and smear layer removal properties of lasers. This in vitro study aimed to compare the antibacterial effects of diode lasers of 810 nm and 980 nm wavelength on Enterococcus faecalis (E. faecalis) biofilm in the root canal system. Materials and methods: Fifty single-canal human anterior teeth were cleaned, shaped, sterilized and rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Previous studies on the antimicrobial effects of diode laser irradiation were mainly conducted in medicine and were focused on pathogenic bacteria such as Enterococcus faecalis and Escherichia coli. Nevertheless, higher values of average laser power than in this paper were most often applied (Beer et al, 2011;Asnaashari et al, 2016;Olivi et al, 2016;Dai et al, 2018), with similar ones applied less often (Tosun et al, 2012;Sadık et al, 2013).…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies on the antimicrobial effects of diode laser irradiation were mainly conducted in medicine and were focused on pathogenic bacteria such as Enterococcus faecalis and Escherichia coli. Nevertheless, higher values of average laser power than in this paper were most often applied (Beer et al, 2011;Asnaashari et al, 2016;Olivi et al, 2016;Dai et al, 2018), with similar ones applied less often (Tosun et al, 2012;Sadık et al, 2013).…”
Section: Discussionmentioning
confidence: 47%
“…The use of diode lasers, in addition to conventional endodontic therapy, has recently been proposed in RCT [16]. Various researchers have observed effective disinfection of the root canal by diode laser irradiation [17][18][19]. Due to the large water transmission capacities of diode lasers (810, 940 and 980-nm wavelengths), they can reach bacteria in deeper layers of dentinal tubules [20].…”
mentioning
confidence: 99%
“…Study has shown that the bactericidal effect of an 810-nm diode laser is better than that of a 980-nm laser, because of greater penetration into tissue. 7 As shown in this case, the 980-nm diode laser surgery might have some advantages over the conventional surgery of pregnancy epulis resection. Firstly, the 980-nm diode laser surgery causes little trauma and almost no bleeding.…”
Section: Discussionmentioning
confidence: 67%